Dismissed With Prejudice - Jance, J.A. (New York Avon Books, 1989)
Japanese businessman Tadeo Kurobashi had many passions, including computers, poetry, money, and Samurai lore. So his suicide method of choice would naturally be the ancient art of seppuku- what the uninitiated call hara-kiri. But despite the bloody samurai sword Kurobashi clutches tightly in his lifeless hand, Seattle detective J.P. Beaumont senses the dead software magnate played a less active role in his own demise. Because glaring errors have been made in the time-honoured Asian death ritual- which has Beau looking for someone with a less traditional passion- cold-blooded murder!
Keywords: Fiction